Utilization of an unstable plasmid and the I-SceI endonuclease to generate routine markerless deletion mutants in Francisella tularensis - Horzempa, Joseph (2009)
We engineered an efficient system to make Francisella tularensis deletion mutations using an unstable, poorly maintained plasmid to enhance the likelihood of homologous recombination. For counterselection, we adapted a strategy using I-SceI, which causes a double-stranded break in the integrated suicide vector, forcing a second recombination to mediate allelic replacement.